1972
DOI: 10.1073/pnas.69.12.3779
|View full text |Cite
|
Sign up to set email alerts
|

Altered Chloroplast Ribosomal Proteins Associated with Erythromycin-Resistant Mutants in Two Genetic Systems of Chlamydomonas reinhardi

Abstract: The phenotype of several erythromycin-resistant mutants of Chiamydomonas reinhardi was further characterized in terms of the electrophoretic properties of their chloroplast ribosomal proteins. In mutant ery-M2d a single protein of the large (52 S) subunit has altered properties, which probably result from a change in its primary sequence. This mutation is inherited in a Mendelian manner. In mutant ery-Ula, which is inherited in a uniparental manner, a different single protein of the 52 S subunit is altered. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

1973
1973
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(28 citation statements)
references
References 24 publications
1
27
0
Order By: Relevance
“…An altered protein of the 30S subunit has been detected in mutant strains carrying the sm2 gene (Ohta, Inouye, and Sager, in preparation). Further supporting evidence comes from studies in which a non-Mendelian erythromycin resistant strain was shown to contain chloroplast ribosomes with reduced erythromycin binding capacity (10) and with an altered twodimensional gel electrophoretic pattern as compared with wild type (12). In a non-Mendelian spectinomycin resistant strain, chloroplast ribosomes were reported to have lost spectinomycin-binding ability (11), and changes in sedimentation constants have been reported for chloroplast ribosomes from non-Mendelian strains resistant to streptomycin-, spectinomycin, and to neamine (9).…”
Section: Methodsmentioning
confidence: 90%
See 1 more Smart Citation
“…An altered protein of the 30S subunit has been detected in mutant strains carrying the sm2 gene (Ohta, Inouye, and Sager, in preparation). Further supporting evidence comes from studies in which a non-Mendelian erythromycin resistant strain was shown to contain chloroplast ribosomes with reduced erythromycin binding capacity (10) and with an altered twodimensional gel electrophoretic pattern as compared with wild type (12). In a non-Mendelian spectinomycin resistant strain, chloroplast ribosomes were reported to have lost spectinomycin-binding ability (11), and changes in sedimentation constants have been reported for chloroplast ribosomes from non-Mendelian strains resistant to streptomycin-, spectinomycin, and to neamine (9).…”
Section: Methodsmentioning
confidence: 90%
“…The pattern of subunit localization, mirroring that found in bacterial ribosomes (8) as well as the low levels of cross-resistance between mutants, provide strong, albeit indirect, evidence that each of the mutant genes responsible for resistance codes for a chloroplast ribosomal protein. Several lines of evidence 1715 that non-Mendelian mutations to drug resistance in Chlamydomonas induce alterations in chloroplast ribosomes have been previously reported (7,(9)(10)(11)(12)(13).…”
mentioning
confidence: 99%
“…Considering the different patterns of inheritance of our two mutants, it seems that two different proteins of the 30 S subunit are altered, so that nuclear and cytoplasmic gene products are present in the 30 S subunits. Similarly Mets and Bogorad [4] found in the 50 S subunit of a Mendelian and of an uniparental erythromycin-resistant mutant of Chlamydomonas reinhardi different altered ribosomal proteins. Both mutated ribosomal proteins in sr 3 and sr35 cause the same loss of binding capacity for dihydrostreptomycin to the 30 S subunit.…”
Section: Resultsmentioning
confidence: 66%
“…In this connection a comparative study of the ribosomes from organelles and cytoplasm is of great importance. For the investigation of chloroplast ribosomes and chloroplastcytoplasmic interactions the unicellular green alga Chlamydomonas reinhardi is widely used [3], and mutants with altered 70 S ribosomes have been decribed [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, 0 :4 Chloroplast biogenesis requires cytoplasmically synthesized proteins as well as those of chloroplast origin. Mutant strains of plants (12,23,26) and algae (13,16) deficient in chloroplast ribosomes have proven useful in the study of the interdependence of the chloroplast and nuclear genomes. Among these, the chloroplast ribosome-deficient mutant of Chlamydomonas reinhardtii, ac20crl, has been characterized in some detail (e.g.…”
mentioning
confidence: 99%